PERLINDUNGAN HUKUM BAGI PENERIMA FIDUSIA SEBAGAI PIHAK YANG LEMAH DALAM SUATU PERJANJIAN JAMINAN FIDUSIA DI LEMBAGA PERKREDITAN DESA (LPD) DESA PAKRAMAN BULELENG - Galih Adi Pradana, Made Bagus; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2015)
This article discusses the legal protection that can be provided to the creditors in a fiduciary or fiduciary agreements. Fiduciary Warranty gives fiduciary control of the object is still in the hands of the giver fiduciary, so in this case the fiduciary susceptible to losses if the debtor has no good faith in carrying out the fiduciary agreement. The problems faced are: whether the weaknesses are owned by the lender in an agreement fiduciary at Lembaga Perkreditan Desa (LPD) Desa Pakraman Buleleng ? And how can the legal protection given to the fiduciary in the fiduciary agreement ? The research method used is the method of empirical research with primary data and secondary data.The results of the research conducted, it can be seen that the weaknesses in the implementation of the agreements held in fiduciary Lembaga Perkreditan Desa (LPD) Desa Pakraman Buleleng regarding the imposition of fiduciary only by deed under the hand and is not registered at the registration office fiduciary. In the implementation of the legal protection of creditors provided for in Law No. 42 Year 1999 on Fiduciary, namely the imposition of fiduciary deed which shall be notarized, and confirmed by the registration of the deed.
Keywords: legal protection, fiduciary, agreements, guarantees